2022
DOI: 10.2147/rmhp.s377378
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Results of China’s Fiscal Medical and Health Expenditure

Abstract: To evaluate the resulting level of fiscal medical and health expenditure in China, and to provide the scientific basis for further improving fiscal medical and health service capacity in China. Patients and Methods:The data envelopment method and Gini coefficient method were used to analyze the efficiency and regional fairness of fiscal medical and health expenditure results by using the relevant provincial and municipal data of China from 2007 to 2019. Results: 1.Overall, from 2007 to 2019, the total expendit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…In addition, it is worth noting that the most previous studies have concluded that government health expenditure positively affects healthcare efficiency ( 18 ), but our findings yield the opposite conclusion. This may be for the following two reasons: First, there are pronounced regional differences in Chinese government health expenditure ( 76 ), with an overall tendency to favor regions with higher economic levels ( 77 ), and given regional disparities in economic development, government health expenditure has had other impacts on PHC institutions of various regions. Second, COVID-19 has posed a significant challenge to the PHC system ( 10 , 78 ), and efficiency must be improved despite the continuous increase in government investment in health.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is worth noting that the most previous studies have concluded that government health expenditure positively affects healthcare efficiency ( 18 ), but our findings yield the opposite conclusion. This may be for the following two reasons: First, there are pronounced regional differences in Chinese government health expenditure ( 76 ), with an overall tendency to favor regions with higher economic levels ( 77 ), and given regional disparities in economic development, government health expenditure has had other impacts on PHC institutions of various regions. Second, COVID-19 has posed a significant challenge to the PHC system ( 10 , 78 ), and efficiency must be improved despite the continuous increase in government investment in health.…”
Section: Discussionmentioning
confidence: 99%
“…Academic research on fiscal expenditure efficiency has become more mature, while aging-related research has focused on livelihoods. Studies have found that fiscal expenditure efficiency is generally better in the eastern and central regions of China than in western ones [41][42][43]; social security expenditure efficiency varies significantly between regions [44]; healthcare expenditure efficiency values are generally on the rise [45]; healthcare expenditure efficiency is generally higher in the central, western, and northeastern regions than in eastern ones [46]; and the fiscal expenditure efficiency of basic public services, including education, healthcare, and social security, has a clear trend of convergence within each region [47].…”
Section: Introductionmentioning
confidence: 99%